Cine‐Substitution Reactions of Metallabenzenes: An Experimental and Computational Study. Issue 33 (10th July 2013) - Wang, Tongdao; Zhang, Hong; Han, Feifei; Long, Lipeng; Lin, Zhenyang; Xia, Haiping
Abstract Alkali‐resistant osmabenzene [(SCN)2(PPh3)2OsCHC(PPh3)CHCICH] (2) can undergo nucleophilic aromatic substitution with MeOH or EtOH to give cine‐substitution products [(SCN)2(PPh3)2OsCHC(PPh3)CHCHCR] (R=OMe (3), OEt(4)) in the presence of strong alkali. However, the reactions of compound 2 with various amines, such as n‐butylamine and aniline, afford five‐membered ring species, [(SCN)2(PPh3)2OsCHC(PPh3)CHC(CHNHR′)] (R′=nBu(8), Ph(9)), in addition to the desired cine‐substitution products, [(SCN)2(PPh3)2OsCHC(PPh3)CHCHC(NHR′)] (R′=nBu(6), Ph(7)), under similar reaction conditions. The mechanisms of these reactions have been investigated in detail with the aid of isotopic labeling experiments and density functional theory (DFT) calculations. The results reveal that the cine‐substitution reactions occur through nucleophilic addition, dissociation of the leaving group, protonation, and deprotonation steps, which resemble the classical "addition‐of‐nucleophile, ring‐opening, ring‐closure" (ANRORC) mechanism. DFT calculations suggest that, in the reaction with MeOH, the formation of a five‐membered metallacycle species is both kinetically and thermodynamically less favorable, which is consistent with the experimental results that only the cine‐substitution product is observed. For the analogous reaction with n‐butylamine, the pathway for the formation of the cine‐substitution product is kinetically less favorable than the pathway for the formation of a five‐membered ring species, but is much more thermodynamically favorable, again consistent with the experimental conversion of compound 8 into compound 6, which is observed in an in situ NMR experiment with an isolated pure sample of 8.